Preparation and method of insulation spraying material for cross arm side of power transmission tower
By using the double -component spraying materials prepared by the use of isocyanate prefabricated and amine compounds, the problem of pollution and shedding of RTV coatings in severe pollution and high -radiation environment, realizing efficient and uniform insulation coating formation, improving machinery And electrical performance.
Patent Information
- Application Number
- CN202411669408.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-21
- Publication Date
- 2025-01-24
AI Technical Summary
Existing RTV coatings are prone to pollution accidents in areas with severe air pollution, and are prone to peeling, powdering or even falling off under strong radiation and high humidity and heat environments, making it difficult to form a thick insulating protective layer.
A two-component spray material is prepared using isocyanate prepolymer and amine compounds, and is sprayed onto the surface of the aluminum plate through a spray gun. After curing, a polyurea resin coating is formed, and the filler ratio is optimized to improve mechanical properties and electrical insulation properties.
Achieve fast solidification, uniform thickness insulation coating, improve electrical insulation performance and mechanical strength, enhance weather resistance and anti -aging performance, and avoid the problem of pollution accidents and coating off the problem.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of coatings, and in particular to a preparation method of an insulating spray material for a cross arm side of a transmission tower. Background Art
[0002] In areas with severe industrial pollution, the surface contamination density of RTV-coated insulators increases significantly due to the long-term deposition of pollutants in the atmosphere, and the probability of pollution accidents also increases significantly. Since the RTV water angle is less than 110° and the rolling angle is large, water droplets are easy to condense on the surface of RTV materials under conditions such as fog, rain or condensation, and it is difficult to roll. When the condensation phenomenon is serious, the water droplets will dissolve the charged particles in the pollutants to form a large area of conductive water film, which makes the insulator very easy to flash on the surface. In addition, many survey reports in recent years have shown that under the influence of typical subtropical climates such as strong radiation and high humidity and heat unique to the southern region, the operation of RTV coatings not only has serious surface contamination problems caused by environmental pollution, but also faces the risk of peeling, powdering and even falling off due to ultraviolet aging. Long-term ultraviolet radiation will destroy the molecular chain of RTV silicone rubber and change its chemical structure, thereby causing the RTV coating to lose its hydrophobicity and the contamination flashover voltage to drop seriously.
[0003] At present, the application scenario of RTV coating is mainly insulators. There is still a gap in the spray material on the cross arm side. In addition, RTV has a long curing time and it is difficult to form a thick insulating protective layer on the surface. A high-insulation fast-curing spray material is urgently needed to fill the gap in the industry. If polyurea material is used as a substitute, its thermal conductivity is still somewhat inferior to RTV material. Summary of the invention
[0004] In view of the shortcomings of the prior art, the present invention provides a method for preparing an insulating spray material on the cross arm side of a transmission tower, which solves the problems raised in the above background technology. To achieve the above purpose, the present invention is implemented through the following technical scheme: a method for preparing an insulating spray material on the cross arm side of a transmission tower, comprising the following steps:
[0005] Step 1, synthesis of isocyanate prepolymer component A: 75 mmol of 4,4-methylenebis(phenyl isocyanate) and 11.25 mmol of polyether polyol were added into a condensation reflux magnetic stirring device and reacted for 3 hours under a nitrogen atmosphere at 80° C. to form isocyanate prepolymer component A;
[0006] Step 2, synthesis of amine compounds of component B: 7.6mmol of 33-dichloro-44-diaminodiphenylmethane and 3.25mmol of amino-terminated polyether were added with 15ml of silane coupling agent and five fillers with a mass ratio of kaolin: boron nitride of 1:1, 1.2:1, 1.5:1, 1:1.5, and 1:1.2 (1 mass part in each ratio is 0.5g) were added and mixed for 5 hours. The obtained B components with five different mass ratios of fillers were named 1#, 2#, 3#, 4#, and 5# respectively;
[0007] Step 3: Add component A and component B into the material pipe of the cross arm spray gun in appropriate proportions and connect the spray gun to an air compressor above 600 kPa to spray the mixture onto the surface of the aluminum plate cleaned with anhydrous ethanol. After spraying, the material is cured at room temperature and sprayed repeatedly 2 to 3 times to increase the thickness of the coating to form a polyurea resin coating.
[0008] Preferably, the molecular weight of the polyether polyol in the component A in the step 1 is 4000 g / mol and the purity of the nitrogen used is 99.99%.
[0009] Preferably, the mixing ratio of the amine compound and the silane coupling agent in the component B in the step 2 is 5:1.
[0010] Preferably, the reaction temperature in step 1 is maintained at 80°C ± 5°C and the stirring rate is 300 rpm. In step 2, the five different kaolin and boron nitride filler mass ratios can be adjusted according to actual test results to achieve optimal mechanical properties and electrical insulation properties.
[0011] Preferably, the aluminum plate after spraying in step 3 needs to be cured at room temperature for 24 hours and then heat-cured at 120° C. for 2 hours to ensure that the weather resistance and electrical insulation performance of the coating meet the expected standards.
[0012] Preferably, the molecular weight of the polyether polyol in step 1 should be 4000 g / mol. The molecular ratio of isocyanate containing at least 4 hydroxy groups should be controlled at 0.67:1 to ensure the reactivity of the prepolymer. The purity of nitrogen used in the reaction process should be 99.99% to ensure that there is no moisture or impurities in the reaction environment to avoid affecting the reaction effect. The reaction temperature should be strictly controlled within the range of 80°C ± 5°C. Too high a temperature will cause the reaction to be too fast and affect the product quality; too low a temperature may lead to incomplete reaction.
[0013] Preferably, the stirring rate in step 1 is controlled at 300 rpm to ensure that the reactants can be fully mixed to avoid excessively high or low local temperatures. The reaction time is controlled to be 3 hours. During this time, component A will react completely to form an isocyanate prepolymer with high viscosity and appropriate reactivity. After the reaction is completed, the product should be cooled and a preliminary analysis should be performed to ensure that its molecular structure meets the requirements. Infrared spectroscopy (FTIR) analysis can be used to detect the consumption of isocyanate groups to ensure the quality of the prepolymer.
[0014] Preferably, the purity of the amine compound 33-dichloro-44-diaminodiphenylmethane in step 2 reaches more than 99% to ensure the adequacy of the reaction and the stability of the final product. The selection of fillers: The mass ratio of kaolin and boron nitride should be adjusted according to different experimental test results. The mechanical and electrical performance tests are required to determine the optimal ratio. Stirring is carried out under nitrogen protection to prevent moisture and oxygen in the air from having a negative impact on the reaction. The stirring time should be 5 hours to ensure that the reaction is complete and the filler and the amine compound can react fully. It is recommended to use a magnetic stirrer or a high shear stirrer to ensure the uniformity of the material. The type of silane coupling agent used is 3-aminopropyl triethoxysilane. The mass of the coupling agent should be 5% of the total reactant mass.
[0015] Preferably, the mass ratio of component A to component B in step three should be controlled between 1:1.05 and 1:1.2 to ensure the proper curing speed and performance stability of the resin. This ratio should be fine-tuned according to different environmental conditions (such as humidity, temperature, etc.). The pressure used during spraying should be greater than 600kPa to ensure that components A and B can be fully mixed in the spray gun. The nozzle diameter of the spray gun is 2mm. The spraying distance should be 150mm±10mm. Spraying should be uniform and continuous to avoid excessive thickness or thinness of local coating. The aluminum plate after spraying needs to be cured at room temperature for 24 hours to ensure surface drying and curing effect. During the curing process, the temperature should not exceed 30°C to avoid high temperature causing material performance degradation. After curing at room temperature for 24 hours, the aluminum plate is placed in an oven at 120°C for heat curing for 2 hours to ensure that the molecular structure of the polyurea coating is stable and its anti-aging performance is enhanced. The thickness of the coating after curing should reach 200μm~300μm to ensure good electrical insulation and mechanical strength.
[0016] A performance test method for the insulation spray material on the cross arm side of a transmission tower, including the following test methods:
[0017] S1: Electrical performance test:
[0018] Insulation resistance test: Use a high voltage insulation resistance tester (test voltage is 5000V) to test the insulation resistance of the coating to ensure that it is not less than 10^9Ω·m;
[0019] Dielectric strength test: The dielectric strength of the coating measured by the electrical breakdown test method (IEC 60243-1 standard) under standard test conditions is required to be no less than 25kV / mm;
[0020] S2: Mechanical properties test: Tensile strength test: Use a tensile testing machine to test the tensile strength of the polyurea coating, and the tensile strength is required to be above 15MPa;
[0021] Hardness test: Use a Shore A hardness tester to test the coating surface hardness, which should reach 75 to 85 degrees;
[0022] S3: Weathering test: Place the coating sample in an accelerated aging test chamber (ultraviolet radiation, temperature and humidity cycle) for 300 hours of weathering test. After the test, check whether the coating has cracks, peeling or color changes.
[0023] Compared with the prior art, it has the following beneficial effects:
[0024] The benefits of this application are:
[0025] The present application uses a two-component spraying method using isocyanate prepolymer component A and amine compound component B to spray the cross-arm side of the transmission tower, thereby preventing short-circuit failures caused by bird damage and other factors. The insulating layer formed by the curing of polyurea has a fast curing time and does not form drips, and the shape of the power components can be ignored. The polyurea material produced by indiscriminate spraying of the parts that need to be insulated has high thermal conductivity and insulation. The spraying effect is good and it can effectively adhere to the surface of power components such as cross-arms. DETAILED DESCRIPTION
[0026] The technical solutions in the embodiments of the present invention will be described clearly and completely below in combination with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention rather than all the embodiments. All other embodiments obtained by ordinary technicians in this field based on the embodiments of the present invention without creative work belong to the scope of protection of the present invention.
[0027] In the description of the present invention, it should be understood that the terms "center", "longitudinal", "lateral", "length", "width", "thickness", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside", "clockwise", "counterclockwise" and the like indicating directions or positional relationships are only for the convenience of describing the present invention and simplifying the description and do not indicate or imply that the device or element referred to must have a specific direction, be constructed and operated in a specific direction and therefore should not be understood as limiting the present invention.
[0028] It should be noted that in the description of this patent, unless otherwise clearly specified and limited, the terms "installed", "connected", "connected", and "set" should be understood in a broad sense, for example, they can be fixedly connected, set, or detachably connected, set, or integrally connected, set. For ordinary technicians in this field, the specific meanings of the above terms in this patent can be understood according to specific circumstances.
[0029] In addition, the terms "first" and "second" are only used for descriptive purposes and cannot be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. It is thus defined that the features with "first" and "second" may explicitly or implicitly include one or more of the features. In the description of the present invention, the meaning of "several" is two or more unless otherwise clearly and specifically defined.
[0030] Example
[0031] This embodiment provides a method for preparing an insulating spray material for a cross arm side of a transmission tower, comprising the following steps:
[0032] Step 1, synthesis of isocyanate prepolymer of component A: take 75mmol of 4,4-methylenebis(phenyl isocyanate) and 11.25mmol of polyether polyol, add them into a condensation reflux magnetic stirring device, and react for 3 hours under a nitrogen atmosphere at 80°C to form an isocyanate prepolymer. Component A selects the reaction raw materials 4,4-methylenebis(phenyl isocyanate) and polyether polyol to react in the required molar ratio. Stability during the reaction is ensured by using nitrogen protection to avoid moisture interference. The reaction temperature is controlled within the range of 80°C ± 5°C and the stirring rate is maintained at 300rpm to ensure the uniformity and sufficiency of the reaction. The synthesized prepolymer needs to be tested by infrared spectroscopy (FTIR) to detect the degree of consumption of isocyanate groups to determine whether the reaction is complete. This step lays the foundation for the subsequent synthesis of the core materials of the polyurea coating;
[0033] Step 2, synthesis of component B amine compounds: 7.6mmol of 33-dichloro-44-diaminodiphenylmethane and 3.25mmol of amino-terminated polyether were added with 15ml of silane coupling agent and five fillers with a mass ratio of kaolin: boron nitride (1 mass part in each ratio is 0.5g) were added for mixing and stirring for 5 hours. The B components with five different mass ratios of fillers were named 1#, 2#, 3#, 4#, and 5#, respectively. The synthesis of amine compounds involves the reaction of 33-dichloro-44-diaminodiphenylmethane and amino-terminated polyether. A suitable proportion of silane coupling agent (3-aminopropyltriethoxysilane) was added during the reaction to enhance the bonding force between the filler and the matrix material. In order to ensure that the filler plays a full role in the reaction, kaolin and boron nitride with different mass ratios were used and mixed and stirred for 5 hours. The key to this step is to optimize the filler ratio through mechanical and electrical performance tests to ensure uniform dispersion of the filler in the final material and improve the overall performance of the material;
[0034] Step 3: Add component A and component B into the material pipe of the spray gun on the cross arm side in appropriate proportions and connect the spray gun to an air compressor above 600kPa to spray the mixture onto the surface of the aluminum plate cleaned with anhydrous ethanol. After spraying, the material is cured at room temperature and sprayed repeatedly 2 to 3 times to increase the thickness of the coating to form a polyurea resin coating. During the spraying process, component A and component B are mixed in a specific proportion to ensure their reactivity and stability. A spray gun with a pressure greater than 600kPa is used to ensure that the mixture can be evenly sprayed on the surface of the aluminum plate during the spraying process. During spraying, the nozzle diameter and spraying distance of the spray gun need to be precisely controlled to ensure uniform thickness of the coating. After spraying, the chemical structure of the polyurea coating is stabilized by curing at room temperature for 24 hours and heat curing at 120℃ for 2 hours to enhance its aging resistance and corrosion resistance.
[0035] In step 1, the molecular weight of the polyether polyol in component A is 4000 g / mol and the purity of the nitrogen used is 99.99%. The molecular weight of the polyether polyol is selected to be 4000 g / mol to ensure sufficient molecular chain length, thereby improving the mechanical properties and durability of the polyurea coating. At the same time, the purity of the nitrogen is controlled at 99.99% to ensure that there is no oxygen or moisture in the reaction process that affects the synthesis of the polyurea, further improving the stability and reliability of the final product.
[0036] In step 2, the mixing ratio of the amine compound and the silane coupling agent in component B is 5:1. The ratio of the silane coupling agent is 5:1, which ensures good chemical bonding between the filler and the matrix material during the reaction. This ratio can enhance the interfacial adhesion of the polyurea coating and improve the mechanical strength and chemical resistance of the coating. The silane coupling agent can improve the compatibility between the filler and the resin matrix and thus enhance the overall performance of the coating.
[0037] In step 1, the reaction temperature is maintained at 80°C ± 5°C and the stirring rate is 300 rpm. The reaction temperature is strictly controlled within the range of 80°C ± 5°C to ensure that the reaction of isocyanate and polyether polyol is completely free of excessively high or low temperatures that affect the reaction rate. During the reaction, the stirring rate is set to 300 rpm to ensure that the reactants are fully mixed to promote the reaction. In step 2, the mass ratios of five different kaolin and boron nitride fillers can be adjusted according to actual test results to achieve the best mechanical properties and electrical insulation properties. The mass ratio of the fillers is flexibly adjusted according to the experimental results to optimize the performance of the material. The coating is ensured to have good electrical and mechanical properties by testing different filler ratios.
[0038] In step 3, the aluminum plate after spraying needs to be cured at room temperature for 24 hours and then heat-cured at 120℃ for 2 hours to ensure that the weather resistance and electrical insulation performance of the coating meet the expected standards. The surface of the aluminum plate after spraying needs to be cured at room temperature for 24 hours to ensure the initial curing of the coating to avoid unevenness or poor adhesion on the coating surface. Then, heat-curing treatment at 120℃ for 2 hours is carried out to further improve the hardness and heat resistance of the coating to ensure that the polyurea coating still has stable performance under high voltage and harsh environmental conditions. This heat curing process helps to further cross-link the molecular structure to enhance the weather resistance and anti-aging ability of the coating.
[0039] The molecular weight of the polyether polyol in step 1 should be 4000g / mol. It contains at least 4 hydroxyl groups. The molecular ratio of isocyanate should be controlled at 0.67:1 to ensure the reactivity of the prepolymer. The purity of nitrogen used in the reaction process should be 99.99% to ensure that there is no moisture or impurities in the reaction environment to avoid affecting the reaction effect. The reaction temperature should be strictly controlled within the range of 80℃±5℃. Too high a temperature will cause the reaction to be too fast and affect the quality of the product; too low a temperature may lead to incomplete reaction. The molecular weight of the polyether polyol is 4000g / mol and contains at least 4 hydroxyl groups. Such a molecular structure can ensure high reactivity and stable structure of the polyurea coating. The molecular ratio of isocyanate to polyether polyol is strictly controlled at 0.67:1 to ensure the completeness of the reaction. There is no excess isocyanate group that causes incomplete reaction. The use of nitrogen with a purity of 99.99% further ensures the smooth progress of the reaction to avoid moisture or oxygen affecting the reaction rate.
[0040] In step 1, the stirring rate is controlled at 300 rpm to ensure that the reactants can be fully mixed to avoid local over-high or over-low temperatures. The reaction time is controlled to 3 hours. During this time, component A will react completely to form an isocyanate prepolymer with high viscosity and appropriate reactivity. After the reaction is completed, the product should be cooled and a preliminary analysis should be performed to ensure that its molecular structure meets the requirements. Infrared spectroscopy (FTIR) analysis can be used to detect the consumption of isocyanate groups to ensure the quality of the prepolymer. The stirring rate of 300 rpm helps to ensure that the raw materials are evenly mixed to avoid precipitation of reactants and thus increase the reaction rate. Controlling the reaction time to 3 hours can ensure that component A reacts completely and verify the reaction results by means such as FTIR to ensure that the molecular structure meets the design requirements, providing reliable raw material guarantees for subsequent batching and spraying.
[0041] In step 2, the purity of the amine compound 33-dichloro-44-diaminodiphenylmethane reaches more than 99% to ensure the adequacy of the reaction and the stability of the final product. The selection of fillers: The mass ratio of kaolin and boron nitride should be adjusted according to different experimental test results. The mechanical and electrical performance tests are required to determine the best ratio. Stirring is carried out under nitrogen protection to prevent moisture and oxygen in the air from having a negative impact on the reaction. The stirring time should be 5 hours to ensure that the reaction is complete and the filler and the amine compound can react fully. It is recommended to use a magnetic stirrer or a high shear stirrer to ensure the uniformity of the material. The type of silane coupling agent used is 3-aminopropyl triethoxysilane. The mass of the coupling agent should be 5% of the total reactant mass.
[0042] The mass ratio of component A to component B in step 3 should be controlled between 1:1.05 and 1:1.2 to ensure the proper curing speed and performance stability of the resin. This ratio should be fine-tuned according to different environmental conditions (such as humidity, temperature, etc.) The pressure used during spraying should be greater than 600kPa to ensure that components A and B can be fully mixed in the spray gun. The nozzle diameter of the spray gun is 2mm. The spraying distance should be 150mm±10mm. The spraying should be uniform and continuous to avoid excessive thickness or thinness of local coating. The aluminum plate after spraying needs to be cured at room temperature for 24 hours to ensure surface drying and curing effect. During the curing process, the temperature should not exceed 30℃ to avoid high temperature causing material performance degradation. After curing at room temperature for 24 hours, the aluminum plate is placed in a 120℃ oven for heat curing for 2 hours to ensure the stability of the molecular structure of the polyurea coating and enhance its anti-aging performance. The thickness of the cured coating should reach 200μm~300μm to ensure good electrical insulation and mechanical strength.
[0043] A performance test method for the insulation spray material on the cross arm side of a transmission tower, including the following test method S1: Electrical performance test:
[0044] Insulation resistance test: Use a high voltage insulation resistance tester (test voltage is 5000V) to test the insulation resistance of the coating to ensure that it is not less than 10^9Ω·m;
[0045] Dielectric strength test: The dielectric strength of the coating measured by the electrical breakdown test method (IEC 60243-1 standard) under standard test conditions is required to be no less than 25kV / mm;
[0046] S2: Mechanical properties test: Tensile strength test: Use a tensile testing machine to test the tensile strength of the polyurea coating, and the tensile strength is required to be above 15MPa;
[0047] Hardness test: Use a Shore A hardness tester to test the coating surface hardness, which should reach 75 to 85 degrees;
[0048] S3: Weathering test: Place the coating sample in an accelerated aging test chamber (ultraviolet radiation, temperature and humidity cycle) for 300 hours of weathering test. After the test, check whether the coating has cracks, peeling or color changes.
[0049] When the above equipment is used, isocyanate (NCO) reacts with hydroxyl (OH) in polyether polyol to form polyurethane prepolymer. This reaction is a typical isocyanate-alcohol reaction. Nitrogen (99.99% purity) in the reaction environment avoids interference from moisture and oxygen, ensures smooth reaction and prevents hydrolysis. The temperature is controlled within the range of 80℃±5℃. The stirring rate is 300rpm, which helps to evenly mix the reactants and ensure complete reaction. Infrared spectroscopy (FTIR) is used to detect the degree of consumption of isocyanate groups to determine whether the reaction is complete. The characteristic absorption peak of the isocyanate group in the FTIR spectrum (about 2270cm-1) will gradually disappear as the reaction proceeds. 33-Dichloro-44-diaminodiphenylmethane reacts with the amino-terminated polyether to form an amino compound. This reaction is an addition reaction of isocyanate and amino groups, which provides a basis for the formation of polyurea resin. Kaolin and boron nitride fillers are mixed in different mass ratios. These fillers can improve the mechanical strength, heat resistance and electrical insulation properties of the final coating. The addition of silane coupling agent enhances the bonding force between filler and resin matrix and improves the overall performance of composite materials. The mixing time of filler and amine compound is 5 hours to ensure uniform reaction and good dispersion of filler in matrix material. Components A and B are mixed in proportion and sprayed evenly on the surface of aluminum plate by spray gun. During the spraying process, the nozzle diameter of the spray gun is 2mm and the spraying distance is 150mm±10mm to ensure the uniformity and consistency of the coating. After spraying, the coating is first cured at room temperature for 24 hours to ensure surface drying and preliminary curing effect. Then use a 120℃ oven for heat curing for 2 hours to further enhance the hardness and heat resistance of the coating. After heat curing, the molecular structure of the polyurea coating is further cross-linked to enhance the mechanical strength, aging resistance and corrosion resistance of the coating. Insulation resistance test: Use a high-voltage insulation resistance tester to test whether the insulation resistance of the coating is not less than 10^9Ω·m. Dielectric strength test: According to the IEC60243-1 standard, the dielectric strength of the coating is required to be not less than 25kV / mm. Tensile strength test: The tensile strength of the coating is tested by a tensile testing machine and is required to reach more than 15MPa. Hardness test: Use a Shaw A hardness tester to test the surface hardness of the coating. The hardness is required to be in the range of 75 to 85 degrees. Ultraviolet and temperature and humidity cycling: Use an accelerated aging test chamber to perform a 300-hour weather resistance test on the coating to check whether the coating has cracks, peeling or color changes.
[0050] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited by the above embodiments. The above embodiments and descriptions are only preferred examples of the present invention and are not intended to limit the present invention. The present invention may be subject to various changes and improvements without departing from the spirit and scope of the present invention. These changes and improvements fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.
Claims
1. A method for preparing an insulating spray material for a transmission tower cross arm, characterized in that: The following steps are involved: Step 1, synthesis of isocyanate prepolymer of component A: 75 mmol of 4,4-methylenebis(phenyl isocyanate) and 11.25 mmol of polyether polyol were added into a condensation reflux magnetic stirring device and reacted at 80° C. under a nitrogen atmosphere for 3 hours; Step 2, synthesis of amine compounds of component B: 7.6 mmol of 3,3-dichloro-4,4-diaminodiphenylmethane and 3.25 mmol of amino-terminated polyether were added with 15 ml of silane coupling agent and five fillers with a mass ratio of kaolin: boron nitride of 1:1, 1.2:1, 1.5:1, 1:1.5 and 1:1.2 (1 mass part in each ratio is 0.5 g) were added respectively, and the mixture was stirred for 5 hours to obtain five B components with different mass ratios of fillers, which were named 1#, 2#, 3#, 4# and 5# respectively; Step 3: Add component A and component B into the material pipe of the cross-arm spray gun in appropriate proportions, and connect the spray gun to an air compressor with a pressure of more than 600 kPa to spray the mixture onto the surface of the aluminum plate cleaned with anhydrous ethanol. After spraying, the material solidifies at room temperature and the spraying is repeated 2 to 3 times to increase the thickness of the coating to form a polyurea resin coating.
2. The preparation of the insulation spray material for the cross arm side of a transmission tower according to claim 1, characterized in that: The molecular weight of the polyether polyol in the component A in the step 1 is 4000 g / mol and the purity of the nitrogen used is 99.99%.
3. The preparation of the insulation spraying material for the cross arm side of a transmission tower according to claim 2, characterized in that: The mixing ratio of the amine compound and the silane coupling agent in the B component in the step 2 is 5:
1.
4. The preparation of the insulation spraying material for the cross arm side of a transmission tower according to claim 3, characterized in that: In the step 1, the reaction temperature is maintained at 80°C ± 5°C and the stirring rate is 300 rpm. In the step 2, the five different mass ratios of kaolin and boron nitride fillers can be adjusted according to actual test results.
5. The preparation method of the insulation spraying material for the cross arm side of a transmission tower according to claim 4, characterized in that: The aluminum plate after spraying in step 3 needs to be cured at room temperature for 24 hours and then heat-cured at 120° C. for 2 hours.
6. The preparation method of the insulation spraying material for the cross arm side of a transmission tower according to claim 5, characterized in that: The molecular weight of the polyether polyol in step 1 should be 4000 g / mol. The molecular ratio of isocyanate containing at least 4 hydroxy groups should be controlled at 0.67:1 to ensure the reactivity of the prepolymer. The purity of nitrogen used during the reaction should be 99.99%. The reaction temperature should be strictly controlled within the range of 80°C ± 5°C.
7. The preparation method of the insulation spraying material for the cross arm side of a transmission tower according to claim 6, characterized in that: In the step 1, the stirring rate is controlled at 300 rpm and the reaction time is controlled at 3 hours. After component A is completely reacted, a preliminary analysis is performed to ensure that its molecular structure meets the requirements. Infrared spectroscopy (FTIR) analysis can be used to detect the consumption of isocyanate groups.
8. The preparation method of the insulation spraying material for the cross arm side of a transmission tower according to claim 7, characterized in that: The purity of the amine compound 33-dichloro-44-diaminodiphenylmethane in the step 2 reaches more than 99% to ensure the sufficiency of the reaction and the stability of the final product. The selection of filler: The mass ratio of kaolin and boron nitride should be adjusted according to different experimental test results. Mechanical and electrical performance tests are required to determine the optimal ratio. Stirring is carried out under nitrogen protection. The stirring time should be 5 hours to ensure that the reaction is complete and the filler and the amine compound can react fully. A magnetic stirrer or a high shear stirrer is used. The type of silane coupling agent used is 3-aminopropyltriethoxysilane. The mass of the coupling agent should be 5% of the total reactant mass.
9. The preparation method of the insulation spraying material for the cross arm side of a transmission tower according to claim 8, characterized in that: In the step 3, the mass ratio of component A to component B should be controlled between 1:1.05 and 1:1.
2. The ratio should be fine-tuned according to different environmental conditions (such as humidity, temperature, etc.). The pressure used during the spraying process should be greater than 600 kPa to ensure that components A and B can be fully mixed in the spray gun. The nozzle diameter of the spray gun is 2 mm. The spraying distance should be 150 mm ± 10 mm. The sprayed aluminum plate needs to be cured at room temperature for 24 hours to ensure surface drying and curing effect. The temperature during the curing process should not exceed 30°C to avoid high temperature causing material performance degradation. After curing at room temperature for 24 hours, the aluminum plate is placed in a 120°C oven for heat curing for 2 hours to ensure the stability of the molecular structure of the polyurea coating and enhance its anti-aging properties. The thickness of the coating after curing should reach 200μm to 300μm.
10. A method for testing the performance of the insulation spray material on the cross arm side of a transmission tower according to any one of claims 1 to 9, characterized in that: The following test methods are included: S1: Electrical performance test: Insulation resistance test: Use a high voltage insulation resistance tester (test voltage is 5000V) to test the insulation resistance of the coating to ensure that it is not less than 10^9Ω·m; Dielectric strength test: The dielectric strength of the coating measured by the electrical breakdown test method (IEC 60243-1 standard) under standard test conditions is required to be no less than 25kV / mm; S2: Mechanical properties test: Tensile strength test: Use a tensile testing machine to test the tensile strength of the polyurea coating, and the tensile strength is required to be above 15MPa; Hardness test: Use a Shore A hardness tester to test the coating surface hardness, which should reach 75 to 85 degrees; S3: Weathering test: Place the coating sample in an accelerated aging test chamber (ultraviolet radiation, temperature and humidity cycle) for 300 hours of weathering test to check whether the coating has cracks, peeling or color changes.
Citation Information
Cited By
Quick-drying type polyurea insulating coating with high weather resistance and bird damage prevention and preparation method of quick-drying type polyurea insulating coating
CN122483673A